Chronic transplant glomerulopathy: New insights into pathogenesis. Issue 3 (6th February 2021) - Gokhale, Avantee; Chancay, Jorge; Shapiro, Ron; Randhawa, Parmjeet; Menon, Madhav C.
Abstract: There have been recent significant advances in short‐term outcomes in renal transplantation, however, long‐term allograft survival remains a challenge. With reported incidences as high of 74.5% of chronic graft loss in patients with biopsies showing transplant glomerulopathy (TG), this syndrome represents an important factor for chronic allograft complications. In this review we show an overview of the novel mechanistic insights into pathogenesis of TG, as well as a brief description of the pathology, diagnosis and newer prognostic indices within TG diagnosis. These data raise intriguing roles for cell‐mediated immunity and podocyte stress in TG as well as reinforce previous associations of TG with ABMR. We also delve into management strategies for TG and report the paucity of existing clinical trial data for this prevalent condition in renal transplants.